2008
DOI: 10.1103/physrevlett.101.147204
|View full text |Cite
|
Sign up to set email alerts
|

Simple Glass Models and Their Quantum Annealing

Abstract: We study first-order quantum phase transitions in mean-field spin glasses. We solve the quantum random energy model using elementary methods and show that at the transition the eigenstate suddenly projects onto the unperturbed ground state and that the gap between the lowest states is exponentially small in the system size. We argue that this is a generic feature of all "random first-order" models, which includes benchmarks such as random satisfiability. We introduce a two-time instanton to calculate this gap … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
156
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(165 citation statements)
references
References 28 publications
8
156
0
1
Order By: Relevance
“…The energy gap is therefore very small compared to the ground-state energy and is not an extensive quantity. One usually resorts to numerical methods when computing the energy gap in quantum spin-glasses [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…The energy gap is therefore very small compared to the ground-state energy and is not an extensive quantity. One usually resorts to numerical methods when computing the energy gap in quantum spin-glasses [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…However, short-range models have O(1) local fields, and in fact, so do power-law and infinite-range systems with general p-body interactions. This suggests that the eigenstate-localized phase of the QREM is an exceptional case among long-range models: strict configuration-space localization cannot exist in any model with O(1) local fields, since the introduction of quantum dynamics causes resonant fluctuations.In this paper, we study the eigenstate properties of the quantum p-spin models [25][26][27][28]. Over the past four decades, these models have become paradigms for the mean-field theory of spin glasses [29][30][31][32] Sherrington-Kirkpatrick model (p = 2) [33,34].…”
mentioning
confidence: 99%
“…In this paper, we study the eigenstate properties of the quantum p-spin models [25][26][27][28]. Over the past four decades, these models have become paradigms for the mean-field theory of spin glasses [29][30][31][32] Sherrington-Kirkpatrick model (p = 2) [33,34].…”
mentioning
confidence: 99%
“…Previous work [16][17][18] had argued that a first order quantum phase transition occurs for a broad class of random optimization models. To gain further insight into this matter we study here three optimization problems which had previously been suggested [17,19,20] as good potential candidates for detailed investigation.…”
Section: H(s)mentioning
confidence: 99%